PERUBAHAN PANDANGAN MODERNISM DAN POSTMODERNISM DALAM KONSEP KONSUMSI DAN KONSUMEN - Retnawati, Berta Bekti (Benefit: Jurnal Manajemen dan Bisnis, 2007)
In this article, there is elaborate on various key ideas about consumption andconsumer a theoretical position that we have labeled âpostmodernismâ. By unmaskingthe limitations of modernism that have to do with the onerous nature of its narrowconventionalism, it show that postmodern developments offer alternate visions ofconsumption prosesses that have an emancipatory potential. Postmodernism viewsboth production and consumption are problematized simultaneously, and theconsumer should now be viewed as a producer, as well as a consumer, of symbols andmeanings that are incorporated into the symbolic system, which all human activityhas become.There are many faces of the consumer at different times duringconsumersâ live in the postmodernism perspective.